Unusual phosphine oxidation: new triazolopyridyl-quinolyl phosphine oxide fluorescent dyes1. Issue 38 (30th April 2015) - Ballesteros-Garrido, R.; Abarca, B.; Ballesteros, R.; Colobert, F.; Leroux, F. R.; García-España, E.
<x xml:space="preserve">Abstract</x> 3-(2-Pyridyl)-[1, 2, 3]triazolo[1, 5-a]quinolylphosphines suffer an unusual phosphine oxidation due to their special geometry that allows a σ-donation of the nitrogen (N1) lone pair to phosphorus.